2019
DOI: 10.1002/oby.22463
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue CTGF Expression is Associated with Adiposity and Insulin Resistance in Humans

Abstract: Objective Connective tissue growth factor (CTGF) is an important regulator of fibrogenesis in many organs. This study evaluated the interrelationship among adipose tissue CTGF expression, fat mass, and insulin resistance in humans. Methods This study examined (1) CTGF gene expression in human subcutaneous preadipocytes before and after inducing adipogenesis; (2) relationships among abdominal subcutaneous adipose tissue CTGF gene expression, body fat mass, and indices of insulin sensitivity, including the hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
3
11
0
2
Order By: Relevance
“…Compared with people who are lean, people with obesity have increased expression of genes for collagen I, IV, V, and VI and histological evidence of increased fibrosis, particularly pericellular fibrosis in omental adipose tissue and SAAT (131)(132)(133)(134)(135). In addition, we recently found that adipose tissue expression of connective tissue growth factor (CTGF), a matricellular protein that regulates tissue fibrosis, is positively correlated with body fat mass and inversely correlated with indices of wholebody, liver, and skeletal muscle insulin sensitivity (136). Adipose tissue expression of collagen genes and collagen content are also inversely correlated with insulin sensitivity in people with obesity, and decrease with weight loss (129,(137)(138)(139).…”
Section: Review Series: Mechanisms Underlying the Metabolic Syndromementioning
confidence: 99%
“…Compared with people who are lean, people with obesity have increased expression of genes for collagen I, IV, V, and VI and histological evidence of increased fibrosis, particularly pericellular fibrosis in omental adipose tissue and SAAT (131)(132)(133)(134)(135). In addition, we recently found that adipose tissue expression of connective tissue growth factor (CTGF), a matricellular protein that regulates tissue fibrosis, is positively correlated with body fat mass and inversely correlated with indices of wholebody, liver, and skeletal muscle insulin sensitivity (136). Adipose tissue expression of collagen genes and collagen content are also inversely correlated with insulin sensitivity in people with obesity, and decrease with weight loss (129,(137)(138)(139).…”
Section: Review Series: Mechanisms Underlying the Metabolic Syndromementioning
confidence: 99%
“…All these changes might cause vascular cell damage and angiogenesis. In addition to these changes, necrosis or apoptosis of acinar cells, proliferative and profibrinogenic of growth factors including platelet-derived growth factor (PDGF), TGF-α [21] and connective growth factor (CTGF) [23] are all involved in fibrogenesis. This pathway induces chronic pancreatitis characterized by atrophy and fibrosis of acinar cells, leading to exocrine and endocrine glandular dysfunction [20,21].…”
Section: Effect Of Nafld/ald On Dmmentioning
confidence: 99%
“…Besides, aberrant CTGF expression is associated with many types of malignancies, diabetic nephropathy and retinopathy, arthritis, and cardiovascular diseases. Yoshino, J. showed that CTGF overexpression was associated with adipose tissue expansion and multi-organ insulin resistance in obese subjects (34). Colak, Y. et al demonstrated that CTGF serum levels might be a clinical marker for distinguishing those NAFLD patients with advanced brosis from those who do not (35).…”
Section: Discussionmentioning
confidence: 99%